ASSESSMENT OF THE KNOWLEDGE OF PEOPLE WITH DIABETES MELLITUS ABOUT THE HANDLING AND ADMINISTRATION OF INSULIN - Tomé, Giovanna Maria de Oliveira; Alves, Gabriella Moraes; Arantes, Gustavo Borges de Oliveira; Melo, Jean de Bessa; Moscatto, Janaína Andre (CIPEEX, 2025)
Diabetes mellitus is a chronic endocrine-metabolic disease characterized by hyperglycemia, with glycemic control being crucial for the prevention of micro- and macrovascular complications. Therefore, it is necessary to introduce pharmacological treatments, such as insulin therapy. The process of self-administering insulin is still an obstacle for many patients, so this study aimed to assess the knowledge of insulin users at the Central University Outpatient Clinic (AUC) about the handling and administration of insulin, detecting the rate of errors and correct responses. This was a quantitative, cross-sectional, methodological study approved by the Ethics and Research Committee of the Evangelical University of Goiás. The research was conducted with 50 AUC patients who use insulin and answered a questionnaire designed to assess errors and correct responses regarding insulin handling and administration. The results showed that the highest error rates were related to the amount allowed for use of the same syringe, homogenization of NPH insulin, and cleaning of the vials. On the other hand, the items with the highest accuracy were the correct technique for removing air bubbles from the syringe, contraindications for application in injured areas, and application in a clean place. The results demonstrate that there are significant deficiencies in the knowledge of insulin-dependent patients about the handling and application of insulin, a reality that compromises the effectiveness of treatment, insulin and glycemic control, and increases the risk of complications associated with diabetes. Thus, continuous guidance on insulin application with the patient is essential to ensure greater patient safety and therapeutic effectiveness.